DETERMINANTS CIRCUITS FOR DISTANCE USINGFOUR WHEEL DRIVE OPTOCOUPLER MICROCONTROLLER AT89S51 - Syaiful Gauc; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Komputer, 2008)
In writing that I make with the title "The Determinants of Distance Series Four Wheels For Vehicles Using an optocoupler-based Microcontroller AT89S51" is intended to reduce the numberof accidents, especially for four-wheeled vehicle that almost happen every day either street or highway within the highway. This happens because not all vehicles have a range of security system that functions as a determinant of the distance if the distance a vehicle warner they are too close to another vehicle. Equipment will be placed on the front bumper that will alert you if the distance is too close.